Development of an agilent voltage source for electrical impedance tomography applications - Chitturi V.; Farrukh N. (Asian Research Publishing Network, 2023)
The desirable features of any voltage source used for electrical impedance tomography applications are: Accurate shape of the sinusoidal waveform, constant amplitude of the signal and low output impedance throughout a wide frequency bandwidth. AD9850 synthesizes a pure, programmable sinusoidal waveform up to 5 MHz. The spectrum analyses provides the proof of a stable frequency agile voltage source around 14 dBm for electrical impedance tomography applications and beyond the beta dispersion range at 10 dB attenuation. 2006-2016 Asian Research Publishing Network (ARPN).